2020
DOI: 10.1016/j.forsciint.2020.110551
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum metal deposition enhancement of friction ridge detail on ballistic materials

Abstract: The version presented here may differ from the published version or from the version of the record. Please see the repository URL above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Another test was performed with fingermark on brass tiles and on fired cartridge cases using the VMD method [ 83 ]. The study shows that the method is effective on ballistic brass surfaces.…”
Section: Firearms and Ammunition Miscellaneous Reportsmentioning
confidence: 99%
“…Another test was performed with fingermark on brass tiles and on fired cartridge cases using the VMD method [ 83 ]. The study shows that the method is effective on ballistic brass surfaces.…”
Section: Firearms and Ammunition Miscellaneous Reportsmentioning
confidence: 99%
“…Other sections – The following papers are detailed in other sections of this report: ability of VMD to detect fingermarks on brass plates and fired cartridge cases [ [267] , [268] , [269] , [270] , [271] ] – See Section 4.4.4 ; performance of the sequential processing involving VMD and amino acid reagents on thermal papers [ 272 ] – See Section 4.4.5 ; impact of corrosive substances on fingermark recovery [ 273 ] – See Section 4.5.3 .…”
Section: Fingermark Visualisationmentioning
confidence: 99%
“…VMD – A series of preliminary studies (few donors and/or sebum-rich fingermarks) investigated the ability of VMD to be applied on brass plates and fired cartridge cases [ [267] , [268] , [269] , [270] , [271] ]. Given their preliminary nature, all these studies require further experiments to strengthen their conclusions, which were the following: positive results were obtained with VMD Au/Zn and VMD Ag/Zn [ 268 , 270 ], both studies emphasizing the influence of the donor and the detrimental impact of the firing event. In her comparative studies, Brewer concluded that VMD Al suited best brass rifle cartridge casings [ 267 ], VMD Au/Zn – wad shotgun cartridges [ 267 ], and VMD Ag – brass handgun casings [ 269 ].…”
Section: Fingermark Visualisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Other techniques reported in the literature are electrostatic enhancement (Xu et al, 2017), electrolysis (Nizan et al, 2012) and Scanning Kelvin probe (Williams & McMurray, 2007). However, although these methods may be able to reveal old and weathered fingermarks, they are often time consuming or very expensive, and require highly specialized operators, making them unavailable for routine forensic laboratory exploitation (Christofidis et al, 2018; Costa, Assis, et al, 2020; Pollitt et al, 2020).…”
Section: Nanomaterials To Macromoleculesmentioning
confidence: 99%